2020
DOI: 10.21203/rs.2.20602/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Mindfulness Reduce Maternal Stress and Promote Mother-Infant Bonding in NICU?

Abstract: Purpose Having an infant in the neonatal intensive care unit(NICU) is highly stressful and it implicated in mother infant bonding. This study investigated the relationship between mothers’ dispositional mindfulness and level of stress and quality of bonding.Methods Self-report measures of Dispositional Mindfulness, Parental Stressor Scale, and the Postpartum Bonding Questionnaire were administered to 120 mothers with newborns admitted in the NICUs in three hospitals in Qom city in Iran. The data analysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Indeed, a deterioration of the quality of parenting has been highlighted as an important risk factor for adult and child psychopathology (e.g., the child's emotional and behavioral problems) (Fredriksen et al., 2019), and has been associated with higher levels of parenting stress (Mason et al., 2011). Specifically, during the postpartum period, higher levels of parenting stress, (i.e., perceiving that the demands faced in parenting exceed available coping resources to deal with them (Lazarus & Folkman, 1986) were found to be associated with lower maternal sensitivity (Dau et al., 2019), lower maternal responsivity (Mills‐Koonce et al., 2011), and more impaired mother–infant bonding (Khoramirad et al., 2020). Although a few studies have found high levels of parenting stress during the COVID‐19 pandemic (e.g., Chung, Lanier, & Wong, 2020), no studies have been performed to date that focus on the postpartum period, so the impact of parenting stress on mother–infant bonding during this pandemic period remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a deterioration of the quality of parenting has been highlighted as an important risk factor for adult and child psychopathology (e.g., the child's emotional and behavioral problems) (Fredriksen et al., 2019), and has been associated with higher levels of parenting stress (Mason et al., 2011). Specifically, during the postpartum period, higher levels of parenting stress, (i.e., perceiving that the demands faced in parenting exceed available coping resources to deal with them (Lazarus & Folkman, 1986) were found to be associated with lower maternal sensitivity (Dau et al., 2019), lower maternal responsivity (Mills‐Koonce et al., 2011), and more impaired mother–infant bonding (Khoramirad et al., 2020). Although a few studies have found high levels of parenting stress during the COVID‐19 pandemic (e.g., Chung, Lanier, & Wong, 2020), no studies have been performed to date that focus on the postpartum period, so the impact of parenting stress on mother–infant bonding during this pandemic period remains to be explored.…”
Section: Introductionmentioning
confidence: 99%